Outstanding Indoor Performance of Perovskite Photovoltaic Cells - Effect of Device Architectures and Interlayers - Sagar Jain (Solar RRL, 2019)
Indoor photovoltaics is one of the best sustainable and reliable energy source for low power consumption electronics such as the rapidly growing Internet of Things. Perovskite photovoltaic (PPV) cells with three benchmark device architectures – mesoporous PPV (mPPV) and inverted PPV (iPPV) with alternative hole transporting layers (HTLs), and carbon‐based PPV (cPPV) are studied under a simulated indoor environment. The mPPV cell using typical Spiro‐OMeTAD as the HTL shows the highest maximum power density (Pmax) of 19.9 μW cm−2 under 200 lux and 115.6 μW cm−2 under 1000 lux (without masking), which is among the best of the indoor PV. Interestingly, when PTAA is used as the HTL in the mPPV cell, the Pmax drops to almost zero under indoor light environment while its performance under one sun remains similar. On the other hand, when PEDOT:PSS is replaced by Poly‐TPD as HTL in the iPPV cell, the Pmax under indoor light improves significantly and is comparable to that of the best mPPV cell. This significant difference in indoor performance correlates well with their leakage current. The HTL‐free cPPV cell, prepared by fully up‐scalable techniques, shows a promising Pmax of 16.3 and 89.4 μW cm−2 under 200 and 1000 lux, respectively. A practical scale 5 × 5cm2 cPPV module is fabricated as a demonstration for real applications.